Chemoselective Annulation of 2‐Benzothiazolimines Enabled by Bifunctional Phosphonium Salt: Highly Enantioselective Synthesis of Indole‐fused Cyclic Thiourea Scaffolds. Issue 9 (18th August 2022) - Li, Kehan; Lu, Dongming; Tan, Jian‐Ping; Ren, Xiaoyu; Wang, Tianli
Abstract: A highly efficient chemoselective and stereoselective annulation utilizing 2‐benzothiazolimines as unusual C2‐synthons by thiourea‐based bifunctional phosphonium salt catalysis has been developed. This asymmetric protocol provides a rapid access to highly functionalized and indole‐fused cyclic thiourea scaffolds that bear benzothiazole cores in high yields with excellent both diastereo‐ and enatioselectivities. This transformation proceeds under mild reaction conditions and expands the catalytic potential of phosphonium salt catalysts. Abstract : A highly efficient chemoselective and stereoselective annulation utilizing 2‐benzothiazolimines as unusual C2‐synthons by thiourea‐based bifunctional phosphonium salt catalysis has been developed. This asymmetric protocol provides a rapid access to highly functionalized and indole‐fused cyclic thiourea scaffolds that bear benzothiazole cores in high yields (up to 97%yield), with excellent both diastereo‐ and enatioselectivities(up to >99% ee and >20 : 1 dr ). Mechanism studies disclosed that both hydrogen‐bonding and ion‐pair interactions are crucial for the excellent asymmetric induction.